Pegembangan KATARIAN Sebagai Media Edutainment Untuk Meningkatkan Kemampuan Berhitung Perkalian Siswa Kelas 3 Sekolah Dasar - Rika Yulia; Isrok'atun; Ani Nur Aeni (Elementary Teacher Education Program, Majalengka University, 2024)
The purpose of this research is to develop KATARIAN as an Android-based Edutainment media to improve the multiplication calculation skills of class III students at SDN Lebak Gede and find out the feasibility of the media being developed. Apart from that, through this research, it will be known how students' abilities increase before and after using KATARIAN media. This research uses a type of development research with the ADDIE development model. The research instruments used were material expert validation sheets, media experts validation sheets, pretest-posttest question sheets, teacher and student response questionnaires. Data analysis techniques for validation by experts and teachers are measured using a Likert scale, then the pretest and posttest sheets use the N-Gain formula analysis. Meanwhile, media feasibility is measured by teacher and student response questionnaires. From the research results, it is known that this Edutainment-based KATARIAN media is very valid in terms of validation results from material experts and media experts with an average percentage of 96% in the very valid category. Judging from the pretest-posttest results before and after media use, the N-Gain result was 0.6073 with a